Multivariate Analysis of Determinants of Mothers’ Willingness to Provide BCG Immunization to Children as an Effort to Prevent Tuberculosis in the Working Area of Paya Bakong Health Center - Mhd. Hidayatullah; Nurmakiah Nurmakiah; Rosalia Putri; Hafni Zahara (Public Health Journal, 2026)
BCG immunization is one of the essential basic immunizations that provides protection against severe forms of tuberculosis in children. Mothers’ willingness to provide BCG immunization is an important aspect in achieving optimal immunization coverage. This study aimed to analyze the determinants associated with mothers’ willingness to provide BCG immunization in the working area of Paya Bakong Public Health Center. This study employed a quantitative analytical design with a cross-sectional approach. The study was conducted in December 2025 and involved 195 mothers with infants aged 0–11 months. Participants were selected using an accidental sampling technique. Data were analyzed using univariate analysis, bivariate analysis with the Chi-Square test, and multivariate analysis using binary logistic regression. The results showed that 150 respondents (76.9%) were willing to provide BCG immunization, while 45 respondents (23.1%) were unwilling. Bivariate analysis showed that knowledge (p=0.000) and attitude (p=0.000) were significantly associated with willingness to provide BCG immunization, whereas barriers were not significantly associated (p=0.171). In the multivariate analysis, knowledge (p=0.001) and attitude (p=0.002) remained significantly associated with willingness to provide BCG immunization, while barriers were not significant (p=0.718). The regression model explained 29.2% of the variation in willingness to provide BCG immunization. In conclusion, knowledge and attitudes were significantly associated with mothers’ willingness to provide BCG immunization. Therefore, strengthening health education and communication regarding the benefits and importance of BCG immunization is necessary to increase mothers’ willingness to immunize their children.